Sensorized soft robotic glove for continuous passive motion therapy - Haghshenas-Jaryani, Mahdi; Carrigan, Wei; Nothnagle, Caleb; Wijesundara, Muthu B. J. (Proceedings of the ... IEEE/RAS-EMBS International Conference on Biomedical Robotics and Biomechatronics, 2016)
This paper presents the design and development of a sensorized soft robotic glove based on pneumatic soft-and-rigid hybrid actuators for providing continuous passive motion (CPM) in hand rehabilitation. This hybrid actuator is comprised of bellow-type soft actuator sections connected through block-shaped semi-rigid sections to form robotic digits. The actuators were designed to satisfy the anatomical range of motion for each joint. Each digit was sensorized at the tip with an inertial measurement unit sensor in order to track the rotation of the distal end. A pneumatic feedback control system was developed to control the motion of the soft robotic digit in following desired trajectories. The performance of the soft robotic glove and the associated control system were examined on an able-bodied subject during flexion and extension to show the glove's applicability to CPM applications.